Approach to public management in manizales. contributions for sustainability of urban-rural territories (2009)
This investigation is inscribed in the territorial planning context, structured on the theoretical principles of the sustainable environmental development and in the State’s actions on constitutional and legal basis. Public administrative actions of Manizales municipality are reviewed between 2000-2006 period in which three different administrations were assumed. Planning strategies, implementation and following devices have been studied, considering the different dimensions of the development entrusted to the territorial entity, by the elaboration and interpretation of efficacy, efficiency, coherence, continuity, administrative participation and localization of the variable actions and its indicators. Results are given in two different ways, first, related to the supported reflections about the outcome of the application of statistical indicators to variables; second, by the construction of a proposal for territory management and occupation that gives possible work lines to achieve a sustainable development of the territory, assuming as principles the urban-rural interaction, the decentralized and inter-institutional actions, and the regional articulations of the public programs. In this article are primarily reported the first group of results.